Alexey Navalny: A hero of the new time. Issue 1 (March 2022) - Etkind, Alexander
Russian leaders first tried to poison him, then unlawfully imprisoned him, and now are publicly torturing him. His enemies see him as an illegitimate pretender to the Russian throne. His fans are captivated by his ability to survive assassinations and withstand torture. I was among those who nominated Alexey Navalny for the Nobel Peace Prize. Though he has not received it, this failure exposes meaningful though underappreciated truths about Russia and about the world. My story will leap back and forward between Navalny's individual actions, the peculiarities of Putinism, and global issues of neoliberal governance.